Dinamika Kebijakan Keuangan dan Dampaknya terhadap Valuasi Saham dalam Sektor Otomotif Indonesia - Septian, Andri (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2023)
The automotive sector in Indonesia has a key role in the country's economic growth. Automotive company financial policies, such as the use of debt and dividend distribution, have become important topics of discussion in the context of the dynamics of automotive company stock prices. Therefore, this study aims to investigate the effect of debt policy and dividend policy on stock prices of automotive companies in Indonesia. This study uses historical data on debt policy, dividend policy, and stock prices of automotive companies listed on the Indonesia Stock Exchange (IDX) for the last 5 years. Panel regression analysis is used to measure the effect of debt policy and dividend policy on stock prices. The results of the study show that debt policy and dividend policy have a significant influence on the stock prices of automotive companies in Indonesia. More specifically, this study found that the wise use of debt and the right dividend policy can have a positive impact on the stock value of automotive companies.